Comparative Analysis of Population Dynamics and Roosting Preferences of selected Microchiropteran Bats in Tirunelveli District, Tamil Nadu (International Journal of Food and Nutritional Sciences, 2023)
Bats are the second most diverse group of mammals. The objective of this study was to conduct an investigative survey on distribution, roost preferences, and population dynamics of Microchiropteran bats in Tirunelveli District, Tamil Nadu, South India. The comparative analysis with an earlier and current survey of similar objective carried out in the same study area. A total of five species of Microchiropteran bats were selected for this survey. Bats were surveyed through roost identification techniques, which included visual searching, bat presence signs, and sunlight reflection techniques. Population values were analysed through Principal Component Analysis (PCA) and diversity values—Margalef's Index, Simpson's Index, and Shannon's Diversity Index—and Mean Absolute Deviation (MAD) for analysis of roost preference. The result indicates a decline in populations of Hipposideros speoris, Hipposideros fulvus, Megaderma lyra, while Pipistrellus coromandra, and Taphozous melanopogon have increased in their populations. Habitat utilisation, co-occurrence patterns, and threats like habitat destruction, pesticide applications, and restoration of temples were documented as contributing factors for population decline and variation in roost selection. The study reports dramatic variations in bat population and roost site preference with a focus on the implementation of conservation strategies to mitigate Microchiropteran bat threats.